Изучение реакции взаимодействия фторида натрия и средних молибдатов РЗЭ - Перепелица, Александр Петрович; Бондарь, Александр Алексеевич; Крониковский, Олег Игоревич (My University, 2014)
Методом рентгенофазового анализа исследованы продукты твердофазного взаимодействия фторида натрия и средних молибдатов РЗЭ R2(MoO4)2, R – La – Lu, Y, и установлено, что таковыми являются RF3 и NaR(MoO4)2 (I), для (I) установлены параметры тетрагональной ячейки типа шеелита. With method of X-ray diffraction studied the reaction between sodium fluoride and REE molybdates medium (yttrium) at a molar ratio of 2:1 in a vacuum at 5000C for 30 hours. Found that the reaction of fluoride formed REE RF3 and double molybdate NaR(MoO4)2, for which calculated unit cell parameters of scheelite-type tetragonal.
Keywords: рентгенофазовый анализ; средние молибдаты РЗЭ; х-ray diffraction; medium molybdates REE; кафедра харчової хімії